The perceived effect of serious adverse perinatal events on clinical practice. Can it be objectively measured?. (September 2019) - McNamara, Karen; O'Donoghue, Keelin
Abstract: Objective: Obstetrics involves a high degree of clinical risk. While serious adverse events resulting in substantial maternal or neonatal morbidity or mortality are relatively rare it has been shown that exposure to a such an event can have a predominantly negative personal and professional impact on the healthcare professionals who are involved. There is little in the published literature to show an objective change in clinical practice as a result of an adverse event. The aim of this study was to identify if it was feasible to design a study that could objectively demonstrate if a change in labour ward clinical activity occurred in the 28 days following a serious adverse perinatal event. If this proved possible, the second aim was to identify if these changes could be attributed to the preceding adverse event. Study design: This study was conducted in a large tertiary teaching hospital in Ireland. This was a retrospective observational study conducted using data from a 25-month period from August 2013 to September 2015. Six of the most serious adverse perinatal events that occurred over that time period were identified from the hospital's clinical risk register. Various outcome variables in the form of aggregate data on all deliveries that occurred in CUMH for the 28 days preceding and succeeding the events were collected by the lead author. The medical records for each severe adverse perinatal event were reviewed and the clinical case details recorded. Based on these clinical details individual hypotheses were created for each event. Data was analysed using IBM-SPSS. Results: Aggregate data relating to 6180 deliveries was collected and analysed. Data analysis revealed some statistically significant changes in clinical activity in the 28 days following five of the six adverse events. These changes in clinical activity did not, however, always match what we had expected from our original hypotheses. Conclusion: This novel study aimed to identify if it was possible to objectively demonstrate this practice change. We identified some statistically significant changes in clinical activity in the 28 days following five of the six adverse events but were unable to definitively conclude if the change in activity was a direct result of each event.